ASSERTIVENESS OF A LOG LENGTH SENSOR ALLOCATED IN DIFFERENT POSITIONS ON THE HARVESTER HEAD - da Silva, Josiane Maria; Santana, Lucas Santos; Volpato, Carlos Eduardo Silva; da Silva, Ana Beatriz Alves; Goiz, Tauan Bonin (Floresta, 2022)
Wood length variability can affect operational yield and productivity in harvesting and forest transport operations. Assertive lengths meet positive quality criteria for the product to cellulose factory delivered. Therefore, research is needed to assess assertiveness in measuring wood logs’ length. Thus, the objective was to evaluate length sensor accuracy at different positions in the harvester head. The following treatments were defined: sensor coupled in measuring wheel without a protective piece (T1); sensor coupled in measuring wheel with protective piece (T2); sensor coupled in feed roller without protective piece (T3) and sensor coupled in feed roller with protective piece (T4). The study was carried in a eucalyptus plantation destined for the production of cellulose pulp and, through daily measurements of wood log length in the field, 8373 measurements were obtained. Data were submitted to ANAVA, mean tests (Tukey and Scott-Knott), Statistical Process Control (SPC) and frequency distribution. Treatments T1 and T3 presented average length corresponding to 6.46 m and 0.11 and 0.17 m standard deviation, respectively. T2 and T4 presented and average of 6.42 m and standard deviation equal to 0.12 and 0.16 m, respectively. treatment T1 presented assertive distribution frequencies, presenting 80% of the logs processed within the established limit (6.30 and 6.70 m) while T2, T3 and T4 presented 55%, 45% and 40%, respectively. It is concluded that the sensor coupled in measuring wheel and without the protective piece obtained greater accuracy in wood logs final length.